Perancangan Sistem Pendukung Keputusan Metode SAW Untuk Menentukan Guru Terbaik (Studi Kasus : SDN Langenharjo 01) - Rafel Fernando; Muhammad Ilham Aziiz Alfarobi; Yuliana Dewi Proboningrum; Nabilah Maimunah; Karisna Wahyuningtyas (STIKes Ibnu Sina Ajibarang, 2024)
Education is an effective way to improve people's quality of life. The quality of education depends on the quality of the teachers who teach. Teachers have an important role in the growth and development of students at school. SDN Langenharjo 01 evaluates teacher performance in teaching students by selecting the best teachers as a form of appreciation for their performance and also as a form of teacher motivation to improve the quality of teaching students at school. The school still carries out manual calculation processes and does not yet use the system. The aim of this research is to develop a decision support system for determining the best teachers at SDN Langenharjo 01 using the web-based Simple Additive Weighting (SAW) method. This research uses the Agile System Development method, starting with initial planning, then continuing with the analysis and design stages, and ending with implementation and testing. The SAW method calculation shows that Raharja S.Pd is the best teacher with a preference value of 0.9913. Testing of system functionality shows that all functions in this decision support system work as expected